Effect of oblique retroreflection from a vibrating mirror on laser Doppler shift - Agusanto, Kusuma (2020)
A laser Doppler vibrometer (LDV) fails to measure a large out-of-plane vibration of a rotating mirror when the mirror obliquely reflects the laser beam away, causing a signal loss from being detected. To solve this problem, an external retroreflective tape was used to recover the oblique reflection. However, the reading of LDV obtained from the recovered signal is not right because the retroreflection adds extra Doppler frequency shifts to the oblique reflection. Here, we first derive the relationship of Doppler shift to the oblique angle of retroreflection. For the first time with the help of retroreflection, a standard LDV can measure the largely vibrating mirror as well as a high-speed camera, albeit without the need for heavy computation.